English pronunciation online learning as an effort to optimize the learning process in the COVID-19 pandemic situation - Wahyu Budi; Irma Rahmawati; Muhamad Ekhsan (Central Community Development Journal, 2021)
The implementation of community service is carried out in one of the junior high schools located in South Tambun, Bekasi. This community service aims to share knowledge regarding the application of English Pronunciation Learning as an Effort to Optimize the Learning Process in the Covid-19 Pandemic Situation at SMPN 5 Tambun Selatan. The method used is in the form of counseling with practical delivery so that the learning application can be accepted and applied while learning English at SMPN 5 Tambun Selatan during the pandemic or face-to-face learning. The objective of this activity is an effort to improve the quality of human resources, improve skills in terms of mastering the material and communicating in English for participants.